Work-family conflict, work stress and coping strategies among selected call center agents - Emor, Jaeza G.; Quijada, Catherine L. (2009.)
This is a descriptive study aimed to determine the work-family conflict, work stress and coping strategies of call center agents. Results showed that call center agents have a good balance relationship between work and family but high working stress.
Thesis (Undergraduate, Bachelor of Arts in Psychology-Sociology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Call center agents; Family